ANALISIS LARANGAN ANGGOTA DEWAN PERWAKILAN DAERAH MERANGKAP PENGURUS PARTAI POLITIK TERKAIT SISTEM POLITIK DEMOKRASI - Pradita, Elfira; Husodo, Jadmiko Anom (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
This study analyzes and examines the prohibition of members of the Regional Representative Council (DPD) concurrently administrators of political parties and formulates ideal arrangements for the requirements of DPD member candidates regarding the political system of democracy. This research is a legal research that is of a nature perspective, with a legal approach and a conceptual approach. The type of data collected consists of primary legal material and secondary legal material. The data collection technique used is library research. The technical analysis used is a syllogism method that uses a deductive mindset. The results of the study indicate that the prohibition of DPD members and administrators of political parties is right based on (1) a historical analysis of the formation of the DPD; (2) differences in the nature of representatives; and (3) potential conflicts of interest that may arise. The ideal arrangement for the requirements of DPD member candidates is (a) not a political party administrator at least 5 years before nomination (b) domicile requirements for a certain period of time; and (c) organizational / community regional leadership requirements.